Penanaman Karakter Percaya Diri Melalui Keterampilan 4C di Mts Alkhairaat Bobalo - Sukmawati; Minarni; Sunarto Amus; Shofia Nurun Alanur; Roy Kulyawan; Windy Makmur (Journal of Cultural Relativism (JCR), 2024)
Self-confidence is the courage to do something good according to your knowledge and abilities. such as being able to solve problems well and having the courage to appear in public. This research seeks to (1) characterize the lack of self-confidence among students taking citizenship education, (2) explain how 4C skills are applied to increase students' self-confidence at MTs Alkhairaat Bobalo, and (3) identify the factors. which facilitate or hinder the application of 4C skills to develop students' self-confidence. A qualitative approach and descriptive research design were used as research methodology. MTs Alkhairaat Bobalo applies 4C skills in the following way, according to research findings: MTs Alkhairaat Bobalo's efforts to increase self-confident character through the use of 4C skills of critical thinking, communication, collaboration and creativity are integrated into 4C skills. learning process. When students are not ready to learn and time is limited, the effective application of 4C skills at MTs Alkhairaat Bobalo is hampered. One way to help students develop the 4C skills of critical thinking, is to get them used to sharing their thoughts and encouraging questions. However, sometimes, students still struggle with shyness or fear of thinking or asking questions. Students' communication skills in conveying their ideas quickly and clearly are still relatively low. Collaboration, sometimes occurs during group assignments where they can explore their abilities together with their group friends but some of the students themselves cannot work together well. Creative, students can develop the skills they have but usually they cannot develop the skills they have. (3) The obstacles in implementing 4C skills at MTs Alkhairaat Bobalo towards self-confidence are two factors, namely internal factors, when students are not ready to learn and very long distances. As well as external factors, namely the facilities and infrastructure that the school has.